Problematika Proses Pembelajaran Anak Tunarungu Di SLB Ayodya Tulada Surabaya - Putri, Nadya (Journal of Special Education Lectura, 2024)
The aim of this research is to describe the problematic learning process of deaf children in SLB. This type of research uses qualitative research methods with a descriptive approach. The data collection techniques used by researchers in this research were interviews, observation and documentation. The research subjects in this study were deaf students and class teachers. The research results show that there are several problems that occur during the learning process, because students have limitations and also have different characteristics. To overcome this, teachers and schools make various efforts so that these problems can be handled well.